TEACHER RELATIONSHIP AMONG LEARNING DISABLED SENIOR SECONDARY SCHOOL STUDENTS IN RELATIONSTO DEMOGRAPHIC VARIABLES AND SELF-ESTEEM - SARKAR, CHIRANJIT (International Journal of Psychosocial Rehabilitation, 2020)
The effect of demographic variables and self-esteem on teacher relationship among learning disabled students. So, the focus area of the study relates to teachers’ relationship along with learning disabled students. The Objectives of the study are to study and compare teacher relationship among learning disabled senior secondary school students in relation to their Gender, to study and compare teacher relationship among learning disabled senior secondary school students in relation to their Age, to study and compare teacher relationship among learning disabled senior secondary school students in relation to their Parental Income and to study and compare teacher relationship among learning disabled senior secondary school students in relation to their Self-esteem. Here, descriptive school survey method is used to gain intensive knowledge regarding the topic. Through this method the researcher tries to search the actual percentage of senior secondary school students with learning disorder. When Learning disabled students feel happy to explicit their hesitation with their teachers, exhibit more self-confident, self-esteem etc. Teachers play an important contribution to encourage their learning-disabled students. Teachers play a vital role to motivate their learning-disabled students. Here, 82% senior secondary learning-disabled students realized that teachers are conscious about their interest and talent at Paschim Bardhaman in West Bengal. The researcher shows that the success and achievement of learning-disabled students are not only depend on teachers but also parents. The success of learning-disabled students depends on healthy teacher and students’ relationship. The success of learning-disabled students depends on parent peer-teacher relationship (Social Relationship).